Hubungan Harmonis dengan Tuhan, Alam,dan Manusia dalam Pandangan Kelompok Penghayat Kejawen Gunung Kawi (Laboratorium Sosiologi FISIP Universitas Jember, 2023)
Kejawen adherents believe that humans should have a harmonious relationship with God, nature and humans in their lives. This value is believed to be a guideline for life so that they avoid any danger/disaster in life. This study aims to determine the concept of a harmonious relationship with God, nature and humans in the view of the Gunung Kawi kejawen adherents group. In classical theory, Emile Durkheim explained that religion has two categories, namely sacred and profane which are integrated systems of beliefs and practices related to sacred things. This study uses ethnographic methods that produce descriptive data. data collection using participant-observation and non-participant, in-depth interview methods to be used to gather information. The results of the study state that the concept of human harmony in relation to God is contained in the concept of